Geographical Distribution of Technical Efficiency in Indonesian Rice Production during The Period of 1979-1994 - Joko Mariyono (Economic Journal of Emerging Markets, 2006)
Agriculture still plays a key role in Indonesian economic development, but rice pro-duction is still less competitive than that in other countries. One possible cause is low pro-ductivity, which is to some extent dependent on technical efficiency. This study measures the technical efficiency of rice production in five regions, and examines factors determining its variability. This study uses stochastic frontier of production functions to estimate the techni-cal efficiency. The results indicate that variation in rice production is due largely to varia-tion in technical efficiency. Rice production in Bali is the most technically efficient, whereas in Kalimantan, Sulawesi and Nusa-Tenggara are still inefficient. The efficiency is dependent on facilities available in each region, government programs and the quality of land. Thus there is still a considerable opportunity for improvement in productivity of rice farms outside Java and Bali, given the state of agricultural technology for rice production. Improving ag-ricultural facilities, such as water irrigation and training is capable of enhancing productiv-ity of rice. Keywords: technical efficiency, stochastic frontier production function, panel data analysis